An Ultra-Low-Power Oscillator with Temperature and Process Compensation for UHF RFID Transponder - Wang, Yao; Liu, Jiaxin; Xie, Liangbo; Wen, Guangjun (Společnost pro radioelektronické inženýrství, 2013)
This paper presents a 1.28MHz ultra-low-power oscillator with temperature and process compensation. It is very suitable for clock generation circuits used in ultra-high-frequency (UHF) radio-frequency identification (RFID) transponders. Detailed analysis of the oscillator design, including process and temperature compensation techniques are discussed. The circuit is designed using TSMC 0.18μm standard CMOS process and simulated with Spectre. Simulation results show that, without post-fabrication calibration or off-chip components, less than ±3% frequency variation is obtained from –40 to 85°C in three different process corners. Monte Carlo simulations have also been performed, and demonstrate a 3σ deviation of about 6%. The power for the proposed circuitry is only 1.18µW at 27°C.
Keywords: Ultra-low-power; oscillator; temperature; process; compensation; RFID.